2012
DOI: 10.1126/science.1226929
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation of Neurons and Astrocytes by Oncogenes Can Induce Gliomas in Mice

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive malignant primary brain tumor in humans. Here, we show that gliomas can originate from differentiated cells in the central nervous system (CNS), including cortical neurons. Transduction by oncogenic lentiviral vectors of neural stem cells (NSCs), astrocytes, or even mature neurons in the brain of mice can give rise to malignant gliomas. All the tumors, irrespective of the site of injection (initiating population), share common features of high exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
427
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(446 citation statements)
references
References 45 publications
18
427
1
Order By: Relevance
“…It is currently unknown whether most brain tumors originate from mutated NSCs within the perivascular niche [237,238] or if normal cells acquire mutations that cause their dedifferentiation into immature, carcinogenic neural progenitors [239]. Tumorigenesis could take a hierarchical or linear pathway from cancer stem cells to malignant tumor cells or could result from normal tissue losing differentiation markers (e.g., b-Tubulin) and gaining proliferation markers (e.g., Sox2, Nestin) (reviewed in [240]).…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently unknown whether most brain tumors originate from mutated NSCs within the perivascular niche [237,238] or if normal cells acquire mutations that cause their dedifferentiation into immature, carcinogenic neural progenitors [239]. Tumorigenesis could take a hierarchical or linear pathway from cancer stem cells to malignant tumor cells or could result from normal tissue losing differentiation markers (e.g., b-Tubulin) and gaining proliferation markers (e.g., Sox2, Nestin) (reviewed in [240]).…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…Tumorigenesis could take a hierarchical or linear pathway from cancer stem cells to malignant tumor cells or could result from normal tissue losing differentiation markers (e.g., b-Tubulin) and gaining proliferation markers (e.g., Sox2, Nestin) (reviewed in [240]). Within the last few years, dedifferentiation as a mode of action in tumorigenesis has been re-evaluated and re-popularized in a variety of cancers including intestinal [241,242], respiratory [243], breast [244], and brain [239,245]. Molecular evidence from Drosophila revealed that dedifferentiation is associated with the loss of a neural-specific zinc-finger protein Lola-N that normally functions to repress cell cycle genes like cdc25 in post-mitotic neurons [245].…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…We believe this finding may serve as indirect evidence, along with that found in the mouse glioma models, 15,16 to suggest that some GBs may originate from GM. Moreover, the WM FLAIR/T2-weighted hyperintensity of type II lesions may correspond to GB infiltration rather than just edema.…”
Section: Discussionmentioning
confidence: 95%
“…15 Another study also found that a glioblastoma could originate from cortical neurons. 16 However, there is always concern about whether results from animal studies can be transferred to humans. It is not known whether gliomas growing in mice with genetic alterations and different microenvironments resemble spontaneous human GBs.…”
Section: Discussionmentioning
confidence: 99%
“…As is becoming more and more clear, extrinsic factors such as the microenvironment are crucial for stem cell function (30,84). Bidirectional interconversion between non-CSC's and CSC's has been demonstrated in several types of cancer (85)(86)(87). This tumor cell plasticity might be an important reason for therapy failure.…”
Section: Proteasome Activity As a Csc Markermentioning
confidence: 99%